A sensitive HPLC-ECD method for detecting serotonin released by RBL-2H3 cells stimulated by potential allergens. Issue 20 (25th September 2015) - Han, Shengli; Zhang, Tao; Li, Ting; Kong, Liyun; Lv, Yanni; He, Langchong
Abstract : An overview of the strategy for the evaluation of potential allergens by detection of released serotonin from RBL-2H3 cells by a HPLC-ECD method. Abstract : A highly sensitive high performance liquid chromatography-electrochemical detection (HPLC-ECD) method being used to detect released serotonin in real time from rat basophilic leukemia 2H3 (RBL-2H3) cells which can be stimulated by potential allergens was established to evaluate the sensitization of potential allergens. Chromatographic separation was carried out on a Chromolith R Speed ROD RP-18e column (50 mm × 4.6 mm I.D., 2 μm). The linearity of serotonin in samples was good, with correlation coefficients greater than 0.9986 within the corresponding concentration range. The relative standard deviation (RSD) percentages were in the range of 0.72%–2.96% for inter-day precision and in the range of 2.02%–3.48% for intra-day precision. The relative errors (REs) were within ±3.21%. The recovery of serotonin was in the range of 100.98%–101.56%, and the RSDs of recovery were less than 2.28%. The method allows for simple sample preparation, short analysis time, and high sensitivity, specificity, and reliability. This method was successfully used to detect serotonin released by RBL-2H3 cells stimulated by different concentrations of schisandrin A and harpagoside. The results demonstrate that schisandrin A and harpagoside can trigger RBL-2H3 cells to release serotonin in a dose-dependent manner. The study contributes to the further use of evaluation of potential allergens.